Monetary Policy Strategies for Latin America - Mishkin, Frederic S. (World Bank, Washington, DC, 2014)
The authors examine possible monetary policy strategies for Latin America that may help lock in the gains the region attained in the fight against inflation in the 1990s. Instead of focusing the debate about the conduct of monetary policy on whether the nominal exchange rate should be fixed or flexible, the focus should be on whether the monetary policy regime appropriately constrains discretion in monetary policymaking. Three basic frameworks deserve serious discussion as possible long-run strategies for monetary policy in Latin America. The authors examine the advantages and disadvantages of a hard exchange-rate peg, monetary targeting, and inflation targeting, in light of monetary policy's recent track record in several Latin American countries, looking for clues about which of the strategies might be best suited to economies in the region. The answer: It depends on the country's institutional environment. Some countries appear not to have the institutions to constrain monetary policy if discretion is allowed. In those countries, there is a strong argument for hard pegs, including full dollarization, that allow little or no discretion to monetary authorities. In countries such as Chile, which can constrain discretion, inflation targeting is likely to produce a monetary policy that keeps inflation low yet appropriately copes with domestic and foreign shocks. Monetary targeting as a strategy for Latin America is not viable because of the likely instability of the relationship between inflation and monetary aggregates, of which there is ample international evidence. No monetary strategy can solve the basic problems that have existed in Latin American economies for a long time. The authors welcome the recent move in Latin American countries toward inflation targeting, but say no policy will succeed unless government policies also create the right institutional environment.